Principals’ Leadership of Mathematics Teachers’ Professional Development - Braseth, Eskil Ahn (Frontiers in Education, 2021)
Leadership has long been recognized for having a significant impact on teacher learning. While research on development programs for mathematics teachers has suggested a change in focus from teachers being passive participants to becoming active learners in practice-based development programs, little is said about how this change in focus affects the principals’ role as leaders of teachers’ professional development (PD). In response to this, the presented study investigates how a Norwegian school management team facilitates and supports its mathematics teacher’s PD in their first year of participation in a particular practice-based development program. Findings from the study show that supporting teachers’ PD is easier said than done. The study highlights the importance of building teachers’ sense of ownership and having a shared overarching goal for participating in a practice-based development program. Moreover, there must be a structure and a practice for development work at school if a plan for development in practice is to be successfully implemented and fulfill teachers’ need for continuous development support. Based on the findings from this study and the use of cultural historical activity theory (CHAT) and the activity system, the article suggests that at least two prerequisites must be present for practice-based development programs to serve as mediating artifacts for teachers’ PD. First, the roles involved in the development work must be defined so that the work or goal-directed actions divided between the people in the shared community act towards the same object. Second, the school leader needs support in his work as a leader of teachers’ PD.